Abiotic and biotic factors influencing nest-site selection by Halictus rubicundus, a ground-nesting halictine bee - POTTS, SIMON; WILLMER, PAT (Ecological entomology, 1997)
1. The nest‐site selection behaviour of the bee Halictus rubicundus (Christ) was examined both within and across sites in the U.K. Females utilized a range of edaphic and microclimatic conditions when choosing a site to excavate a nest. Factors with broad tolerances included slope and hardness; those with much narrower limits included aspect, soil humidity and soil particle composition. 2. There was a preference for softer soils that were easier to dig within a site with a low overall density, but in much denser aggregations problems of maintaining the structural integrity of a nest led to the utilization of harder soils. 3. The thermal advantages of having a warm nest meant that the most suitable areas were those with a southern aspect and a slope that maximized the absorption of solar radiation. 4. Limited areas of substrate with the most desirable characteristics resulted in gregarious nesting (‘limited substrate hypothesis’). 5. Natal nest‐site fidelity complemented the ‘limited substrate’ hypothesis in producing an aggregation of nests.